Minds Online: Teaching effectively with technology - Talat, Nazia (Indian Journal of Educational Technology, 2021)
This article reviews the book titled, "Minds Online: teaching effectively with technology: by Michelle D. Miller. This review gives an introduction, summarizes the book's contents, analyses the book, and ends with conclusions. Through the nine chapters in this book, Miller explores the cognitive principles that enable better learning using technology. She invokes several cognitive psychological aspects, like attention, memory, thinking, and motivation, essential for learning that could be corroborated with technology. This book is recommended both for on line and offline instructors at college as well as higher secondary level.